Synthesis and blood glucose lowering activity of some novel benzenesulfonylthiourea derivatives substituted with 4-aryl-1-oxophthalazin-2(1H)yl-ones. (June 2014) - Yaseen, Shafiya; Bashir, Rafia; Ovais, Syed; Rathore, Pooja; Samim, Mohammed; Javed, Kalim
Abstract Some new benzenesulfonylthiourea derivatives substituted with phthalazones (2a–q) were synthesized by refluxing the appropriate 4-aryl-1-oxophthalazin-2(1H)yl benzenesulfonamides with isothiocyanate in dry acetone over anhydrous K2CO3. All the synthesized compounds were characterized on the basis of IR, 1H NMR, MS data and elemental analysis. These synthesized compounds (2a–q) at the dose of 20 mg/kg were tested for antihyperglycemic activity in the glucose-fed hyperglycemic normal rat model and among these compounds 2f and 2m showed modest antihyperglycemic activity.